Intermediate Algebra (6th Edition)

Published by Pearson
ISBN 10: 0321785045
ISBN 13: 978-0-32178-504-6

Chapter 10 - Cumulative Review - Page 634: 26


$\frac{(\sqrt 3-3)}{3}$

Work Step by Step

$\frac{-2}{\sqrt 3+3}\times\frac{\sqrt 3-3}{\sqrt 3-3}$ =$\frac{-2(\sqrt 3-3)}{(\sqrt 3+3)(\sqrt 3-3)}$ =$\frac{-2(\sqrt 3-3)}{(\sqrt 3)^{2}-(3)^{2}}$ =$\frac{-2(\sqrt 3-3)}{3-9}$ =$\frac{-2(\sqrt 3-3)}{-6}$ =$\frac{(\sqrt 3-3)}{3}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.